The Physical Oceanography of the Cape Hatt Region, Eclipse Sound, N.W.T. - Buckley, J.R.; De Lange Boom, B.R.; Reimer, E.M. (ARCTIC, 1987)
In the spring and summer of 1980 and 1981, detailed measurements of water temperature, salinity and depth, currents, tidal height and waves were made in the vicinity of Cape Hatt, at the northern end of Baffin Island, N.W.T., in support of the Baffin Island Oil Spill (BIOS) Project. Currents in the region were generally weak, averaging less than 10 cm/s near the surface and about 2 cm/s in the deeper waters. Deep circulation in Ragged Channel, on the western side of Cape Hatt, was usually counterclockwise. On the western side of Cape Hatt, a strong (up to 30 cm/s) northward flowing coastal current existed. It was occasionally reversed by a flood tide or prolonged south winds. Eddies were observed in bays on the western side of Cape Hatt driven by this coastal current. These eddies were clockwise when the flow offshore was northward and counterclockwise when the flow was southward. Evidence was found for an internal M2 tide in Ragged Channel. Some of the variations in the observed currents and density fields were explained with a simple model of this tide. Under-ice density profiles showed a typical well-mixed layer just above freezing temperature that reached to the bottom in the nearshore regions and to about 35 m depth in mid-channel. In the ice-free season, there was a pronounced shallow mixed layer that ranged from 4 to 10 m in depth. Water properties at the bottom of Ragged Channel were essentially unchanged from winter to summer. In the winter, water properties in Z-Lagoon were similar to those in Ragged Channel. In the summer, they showed the result of being cut off from the main body of Eclipse Sound. In Ragged Channel, wave conditions were very mild, not exceeding 20 cm in significant height, while on the eastern side of Cape Hatt, they were worse, up to 1.4 m, but still not severe.Key words: Eclipse Sound, oceanography, currents, tides, internal tides, water temperature, salinity, waves Mots clés: Eclipse Sound, océanographie, courants, marées, marées internes, température de l’eau, salinité, vagues